Legal Basis for the Implementation of Simultaneous General Elections and Regional Elections in Indonesia - Utami, Tanti; Putra, Muhammad; Pratama, Farizky; Putra, Zulfiqar; Rahmadi, Muhammad (Indonesian Journal of Law and Justice, 2025)
This article aims to analyse the legal basis and juridical implications of holding general elections and regional elections simultaneously, while evaluating the effectiveness of applicable laws and regulations, both in terms of general elections and regional elections. The research method used is descriptive-analytical research with a normative legal approach as the main approach, which is based on legislation and related legal literature. This approach is supported by empirical legal analysis to obtain a factual picture of the dynamics of simultaneous elections. The data used is secondary data obtained through literature studies and analysed qualitatively. The results of the study show that the legal basis for simultaneous general and regional elections originates from the 1945 Constitution, specifically Article 1 paragraph (2) and Article 22E, which are then elaborated in Law Number 7 of 2017 concerning General Elections, Law Number -Law Number 10 of 2016 concerning Regional Elections, and reinforced by Constitutional Court Decision Number 14/PUU-XI/2013. Even in emergency situations, this regulation is adaptive through Perppu Number 2 of 2020. The positive implications include increased presidential legitimacy, budget efficiency, and effective public participation. However, the implementation of simultaneous general elections can also give rise to technical complexities, disputes, and institutional capacity constraints. Therefore, regulatory harmonisation and institutional strengthening are necessary so that simultaneous general elections truly become an effective, efficient, and substantial means of democracy in strengthening people's sovereignty and do not give rise to matters that could burden people's sovereignty.